2022
DOI: 10.3390/jpm12060907
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Pharmacological Response to CNS Drugs: A Narrative Review

Abstract: In the last decades, both animal and human studies have neglected female subjects with the aim of evading a theorized intricacy of feminine hormonal status. However, clinical experience proves that pharmacological response may vary between the two sexes since pathophysiological dissimilarities between men and women significantly influence the pharmacokinetics and pharmacodynamics of drugs. Sex-related differences in central nervous system (CNS) medication are particularly challenging to assess due to the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 145 publications
0
12
1
Order By: Relevance
“… 23 In particular, animal studies with rodents have reported that opioid analgesia is more potent in males than in females. 24 Nevertheless, the lack of female rats is a limitation of the present study; therefore, our results are only valid for male rats.…”
Section: Discussionmentioning
confidence: 81%
“… 23 In particular, animal studies with rodents have reported that opioid analgesia is more potent in males than in females. 24 Nevertheless, the lack of female rats is a limitation of the present study; therefore, our results are only valid for male rats.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, even when exposed to the same microbial community, sex-specific responses, can significantly impact the treatment outcomes for restoring intestinal homeostasis [ 88 ]. Similarly, sex-specific interactions between microbiota and pharmaceutical compounds can contribute significantly to variations in drug response, effectiveness, and the occurrence of adverse reactions between males and females [ 89 , 90 ]. Thus, by acknowledging and accounting for sex-specific differences in the gut microbiome, therapeutic approaches can be tailored to achieve more effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the role of sex in fentanyl and other opioid use is more complicated. Men have higher rates of opioid use disorder and opioid-related deaths as compared to women, but women show a stronger craving for drug cues, develop opioid use disorder faster than males, and are more likely to be prescribed opioid analgesics for pain management than men ( Back et al, 2011 ; Wightman et al, 2021 ; Martin et al, 2022 ; Romanescu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%